ADDED VALUE ANALYSIS OF SINGKONG CHIPS ON FAMILY BUSINESS GROUP SIPARE-PARE VILLAGE - Khairunnisa Rangkuti; Ainul Mardhiyah; Andini Dwayani Putri (AGRIUM: Jurnal Ilmu Pertanian, 2015)
Business cassava chips in KUK Sipare-pare Village is one of the businesses at Sipare-pare Village that managed by the use of simply limited technology. The aims of this study was to determine the amount of benefit, feasibility and added value of the business processing cassava into cassava chips at Sipare-pare, Air Putih District, Batu Bara. The basic method used in this research is descriptive method. The determination of the research location was done by intentionally (purposive), KUK Sipare-pare Village,  Air Putih District , Batu Baru. Primary data and secondary data were used by observation, interview and record keeping. Analysis method that used by business analysis to determine the amount of benefit, feasibility and added value. The results showed that the profit earned from the business of processing cassava into cassava chips in a single production process at the KUK Sipare-pare was Rp. 403,518.62, -. with R/C ratio 1.57. Processing of cassava into cassava chips at KUK Sipare-pare Village obtained gross value added of Rp 696,000, - net added value of Rp. 693,518.62, - value added per feedstock Rp 5.800, -/ kg and the value added per worker was Rp. 69,600, - /day.Key words: Analysis, value added, feasibility, cassava chips.